Evaluation of Siddha Diagnostic Methods for Karpavippuruthi with the aid of Conventional Diagnostic Methods (AYUSHDHARA, 2022)
The diagnosis of diseases comprise revealing its causes. In Siddha medical system testimony of causative elements is through the examination of pulse, urine, eyes, study of voice, colour of body, tongue and the status of the digestive system. This system has labored out specific technique of urine exam which incorporates look at of its colour, odor, density, quantity and oil drop spreading pattern. So the study was aimed to decide the sensitivity and specificity of the Siddha diagnostic method for Karpavippuruthi. Applying Siddha system of diagnosis with inclusion and exclusion criteria, clinical study was carried out on persons having the disease Karpavippuruthi. The above stated diagnostic equipment along with wrist circummetric sign had been used for this study. Most patients had the wrist circumference of 8 finger units and a mere range of affected person`s urine, drop of oil took the shape of slowly spread. Similarly, eight fold examinations found out maximum patients had pulse play with Vatha pitham. Bitter taste, pale coloured and coated tongue had been observed in tongue examination. Patient`s urine samples had slight aromatic odor and normal density, normal Enjal and nearly absence of frothy. So it may be concluded that the subsequent Siddha tactics in amalgamation particularly Wrist circummetric sign, oil on urine sign and eight fold examinations differentiate the patients of Karpavippuruthi from the healthy volunteers.